The white-crowned black wheatear (Oenanthe leucopyga) in St. Katherine, Sinai: age related differences in territorial aggression and breeding success - McLeod, Luke (2014)
A bird’s quality, measured through various factors associated with fitness, generally increases with age. Such a change in quality is often accompanied by a change in appearance that functions as a signal of status to conspecifics. An age-related change in appearance occurs in the White-crowned Black Wheatear (Oenanthe leucopyga), a small sedentary passerine bird (Muscipadidae) that inhabits arid habitats. In this species, young birds are black-crowned whilst older birds are white-crowned. This report studied a wild population near St. Katherine, Sinai, to test the hypothesis that white-crowned birds are of a higher quality than black crowned birds. The primary measures of quality discussed in this thesis were breeding success, body-size, levels of territorial aggression, mate-choice, survival rate and territory size. Whilst no significant difference was found in many of these measures, white-crowned birds were found to be significantly more territorially aggressive and were more successful breeders. Evidence of an agerelated assortative mating system was also found in town environments. This report therefore provides evidence that a difference in quality exists between birds of different crown morphs. Should future investigations show crown-colours being used to reduce intraspecific aggressive encounters, this would suggest a signalling function for the crown. Furthermore, general information about the Wheatear’s biology is presented in order to increase our understanding of this species and of birds living in arid environments.